Performance Budgeting: Suatu Alternatif Pencapaian Good Governance - Pratolo, Suryo; Bintoro, Muchamad Imam (Universitas Muhammadiyah Yogyakarta, Indonesia, 2003)
We hope that District Autonomy implementation does not move the Corruption, Collusion Nepotism (KKN) from central government to the central of district. If it is happened, it will make the only part of center district people wealth. To avoid this matter, the district government must manage it financial efectively. One of the district financial management object is district expenditure using the budget mechanism. There are many method in budgeting system. They are line item budgeting and Performance one. Recently, Indonesian characteristic budgeting system is like theÂ line item budgeting that have so many weakness (Baswir, 1999). This article discus about the line item and performance budgeting characteristic. The second characteristic is more advantages than the first relatively. So in this article, the researchers try to promote the district expenditure concept base on performance budgeting. The aim of this article is giving the description about how the performance budgeting support district expenditure management in achieving good governance, so the Indonesian district autonomy can be implemented successfully.